Structural characteristics of reinforced concrete beams and slabs with lightweight blocks infill - Wahyuni, Ade Sri (Curtin University, 2012)
A Lightweight Sandwich Reinforced Concrete (LSRC) section has been developed with a novel use of prefabricated Autoclaved Aerated Concrete (AAC). This LSRC section is a reinforced concrete section in which AAC blocks are used as infill material in the section where concrete is considered ineffective under bending. This technology is suitable to be used for slab and beam.Five beams were prepared to investigate the flexural and shear capacity of the LSRC. Based on the test results, the flexural capacity was found to be almost identical to the capacity of the equivalent solid beam, while the shear capacity was reduced. The shear strength reduction was as expected due to the reduction in the compressive strength of AAC infill material.Furthermore, eight tests were also conducted on four slabs, one solid and three LSRC slabs. Based on the test results, all LSRC slabs exhibited similar behaviour to the equivalent solid slab and had varying shear capacities depending on the profile of AAC blocks infill. The obtained shear capacities were compared with the design values based on several major design codes and found to be within the safety predictions of the codes.ANSYS 12.1 was employed to develop nonlinear finite element models of LSRC beams and slabs. The numerical results agree well with the experimental one. The beams modelled with ANSYS followed the same trend as the actual beam in the linear range, however after the first cracking the loss of stiffness in ANSYS model caused the bigger deflection compared to the actual beam. For slab models, ANSYS overestimates the load deflection behaviour due to the cracks that already available in slabs from the previous test. The crack propagation modelled with ANSYS for beams and slabs shows the cracks in the area of AAC blocks which associates with the brittle failure of LSRC beams and slabs.In General ANSYS can predict the behaviour of the LSRC beams and slabs. The developed model can be used to investigate LSRC members with different structural and loading parameters.The proposed LSRC section will be suitable for large span construction. Themain benefits of this LSRC member are the cost and time savings due to theweight reduction and the less of supporting structure and foundation and the consequent ease of construction.